2019
DOI: 10.1177/0963662519868969
|View full text |Cite
|
Sign up to set email alerts
|

The critical reception of theDSM-5: Towards a typology of audiences

Abstract: Since its initial publication, the Diagnostic and Statistical Manual of Mental Disorders has been the object of criticism which has led to regular revisions by the American Psychiatric Association. This article analyses the debates that surrounded the publication of the Diagnostic and Statistical Manual of Mental Disorders (5th ed.). Building on the concepts of public arenas and reception theory, it explores the meaning encoded in the manual by audiences. Our results, which draw from a thematic analysis of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Nurses and other occupational groups have argued that mental health care ought to be unshackled from psychiatric diagnosis (Lakeman & Cutcliffe 2016). However, regardless of the flaws of the current diagnostic taxonomy which is categorical, descriptive, and aetiologically agnostic (although not always treated that way), it has different meanings and assumes different purposes to different audiences (Roy et al 2019). Further, consumers report that having received a diagnosis of BPD was a turning point to allow the conceptualization and validation of their experiences and recognizing that they are not alone throughout their experience (Ng et al 2019).…”
Section: The Need For Diagnosismentioning
confidence: 99%
“…Nurses and other occupational groups have argued that mental health care ought to be unshackled from psychiatric diagnosis (Lakeman & Cutcliffe 2016). However, regardless of the flaws of the current diagnostic taxonomy which is categorical, descriptive, and aetiologically agnostic (although not always treated that way), it has different meanings and assumes different purposes to different audiences (Roy et al 2019). Further, consumers report that having received a diagnosis of BPD was a turning point to allow the conceptualization and validation of their experiences and recognizing that they are not alone throughout their experience (Ng et al 2019).…”
Section: The Need For Diagnosismentioning
confidence: 99%
“…The medical taxonomy vector revealed certain epistemological and methodological issues and debates that resonate with fields outside sport addiction and the sciences. In a previous article (Roy et al, 2019), we showed that publication of the DSM-5 prompted severe criticism and controversies in the media as several paradigms collided, as in the case of sport addiction (conformist vs. reformist, conflictual vs. constructivist, etc.). These represent classical contemporary debates in mental health, where the boundaries between psychological, biological, and social etiologies are porous.…”
Section: Discussionmentioning
confidence: 98%
“…By the time of publishing DSM-5 in 2013, the continuous medicalization of natural human responses led by APA became increasingly critiqued within psychiatry [e.g., ( 3 )], mental health sector [e.g., ( 4 )], practitioners, and academia in general. Debates surrounding the critical reception of DSM-5 primarily relate to the pseudo-scientific nature of the manual and its normalizing power ( 5 ).…”
Section: Introductionmentioning
confidence: 99%